Mathematical Anxiety as Predictor of Learning Motivation Strategies - Jeovanny Alabata Marticion (Southeast Asian Mathematics Education Journal, 2021)
Empirical findings showed how the mathematical anxiety predicts the academic performance of learners. As a coping mechanism, learners are left with various choices in dealing with subjects involving mathematical concepts. One way of coping with these subjects is a preference for learning motivation strategies. The motivation strategies were categorized into cognitive, meta-cognitive, non-informational resources management and information resources management. However, there is scarce literature on how anxiety could predict the behaviour of an individual accommodation of these strategies. This led the researcher to investigate the predictive behaviour of mathematical anxiety on utilization of learning motivation strategies among senior high school students enrolled in the Science,Technology, Engineering and Mathematics  program. The program was crafted for students who  are inclined towards sciences and mathematics. Results revealed that respondents have a moderate level of anxiety. During the course, anxiety contributes to the level of anxiety of the respondents. The self-regulation strategy was the most commonly utilized learning motivation strategy among respondents, while peer learning was the least utilized among the learning  motivation strategies. However, the bivariate analysis showed anxiety was moderately related to rehearsal, organization, effort regulation, time and study environment, peer learning and help-seeking strategies. Regression analysis was also applied to reveal how anxiety predicts specific learning motivation strategies. Analysis disclosed that anxiety predicts the utilization of effort regulations strategies in learning mathematically inclined subjects. The findings provided a new perspective on how anxiety allows learners to utilize available strategies to understand various concepts. Teachers are encouraged to cultivate aculture of regulation, an environment conducive for learning, peer interaction and access to Internet-based or digital resources for learning.